Characterization of patients with primary biliary cholangitis and autoimmune hepatitis from a community hospital in East Harlem - Priyanka Yerragorla; Divya Nekkalapudi; Ahmed Shady; Nora V. Bergasa (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Background and objectives: Primary Biliary Cholangitis (PBC) and Autoimmune Hepatitis (AIH) are uncommon autoimmune diseases in the United States. There is limited information in regards to those two conditions in Black Americans and subjects of Hispanic ethnicity; thus, we conducted a study to characterize patients with these diseases in a community hospital that serves this type of population Methods: A retrospective review from 2001 to 2017 of all electronic medical records of patients with diagnoses of PBC or AIH according to the International Classification of Diseases (ICD 10) was conducted. This period was chosen because of feasibility.  Results: Fifteen patients with PBC were identified, one of whom was a man, all were of Hispanic ethnicity and all were in precirrhotic stages. The response to Ursodeoxycholic Acid (UDCA) was suboptimal, however, no complications from liver disease were identified during the study period.  Five women with AIH were identified, all were of Hispanic ethnicity, all were treated with prednisone and azathioprine with appropriate response.  Conclusions: Hispanic patients with AIH respond to treatment appropriately. However, patients with PBC exhibited a suboptimal response to UDCA.  Pharmacogenetic studies should be considered in Hispanic patients in regards to the use of UDCA.